TaGSNE, a WRKY transcription factor, overcomes the trade-off between grain size and grain number in common wheat and is associated with root development - Khan, Nadia; Yanfei Zhang; Jingyi Wang; Yuying Li; Xin Chen; Lili Yang; Jie Zhang; Chaonan Li; Long Li; Shoaib-ur-Rehman; Reynolds, Matthew P.; Lichao Zhang; et al. (Oxford University Press, 2022)
Wheat is one of the world’s major staple food crops, and breeding for improvement of grain yield is a priority under the scenarios of climate change and population growth. WRKY transcription factors are multifaceted regulators in plant growth, development, and responses to environmental stimuli. In this study, we identify the WRKY gene TaGSNE (Grain Size and Number Enhancer) in common wheat, and find that it has relatively high expression in leaves and roots, and is induced by multiple abiotic stresses. Eleven single-nucleotide polymorphisms were identified in TaGSNE, forming two haplotypes in multiple germplasm collections, named as TaGSNE-Hap-1 and TaGSNE-Hap-2. In a range of different environments, TaGSNE-Hap-2 was significantly associated with increases in thousand-grain weight (TGW; 3.0%) and spikelet number per spike (4.1%), as well as with deeper roots (10.1%) and increased root dry weight (8.3%) at the mid-grain-filling stage, and these were confirmed in backcross introgression populations. Furthermore, transgenic rice lines overexpressing TaGSNE had larger panicles, more grains, increased grain size, and increased grain yield relative to the wild-type control. Analysis of geographic and temporal distributions revealed that TaGSNE-Hap-2 is positively selected in China and Pakistan, and TaGSNE-Hap-1 in Europe. Our findings demonstrate that TaGSNE overcomes the trade-off between TGW/grain size and grain number, leading us to conclude that these elite haplotypes and their functional markers could be utilized in marker-assisted selection for breeding high-yielding varieties.